Investigating the use of environmental tableware based on the theory of planned behavior - Tu, Jui-Che; Chen, Yu-Yin; Lee, Yi-Lin; Wang, Xiao-Lin (Environment, development and sustainability, 2021)
According to the statistics of the Environmental Protection Administration in Taiwan, the average usage amount of disposable tableware is about 59,000 tons year. Disposable tableware waste always causes serious pollution to the environment. The aim of this study is to explore the problem of disposable tableware garbage pollution with respect to different impact factors, and increase the usage of eco-friendly tableware. The subjects of this study are the undergraduates and graduates of the colleges in Taiwan. This research adopted the theory of planned behavior to investigate the relationship between user's behavior and cognition and designed questionnaires through expert interviews to advocate reducing the usage of disposable tableware. 550 college students were invited as the subjects to answer the narrative questionnaires and calculate the score of each questionnaire based on Likert scale. A series of data analysis methods, including reliability analysis, Pearson’s correlation analysis, and regression analysis etc., were adopted and programmed in Statistical Product and Service Solutions. The research results show that the usage of eco-friendly tableware has a positive impact on behavioral intentions, attitudes, subjective norms, and perceived behavioral control. This study also learns that governments, industries, environmental protection, and community groups are closely related and interact with each other; their eco-friendly policy can influence users to undergo behavioral changes as well as encourage them to reject the use of disposable tableware. The conclusions would be helpful for policy makers to take effective actions to guide public behaviors and promote public participation in using eco-friendly tableware.